In silico analysis of some mutation targeting pncA gene of Mycoabcterium tuberculosis - Barrientos-Adrian, K. Y.; Flores Gracia, J.; Molina-Torres, C.; Venegas-Barrera, C.; Guevara-Guerrero, G.; Rendón-Pérez, A. (Acta Universitaria, 2020)
Pyrazinamide is a prodrug used in infections against Mycobacterium tuberculosis and its resistance is mainly due to mutations in the pncA gene. In this study, the detection of point mutations of this gene was performed in clinical isolates from the State of Nuevo León. Three-dimensional models of the pyrazinamidase enzyme were made by sequencing and using computational tools. The presence of important mutations in eight samples was observed, and in two of them termination codons are shown. The analyzes performed showed that the Q10P and W68S mutations structurally affected the active site. The P62L and D63A mutations occur in an important site; however, the enzyme remains stable. On the contrary, when the S179R mutation is analyzed, the enzymatic function is found to be highly unstable.